2009
DOI: 10.1590/s1020-49892009000300008
|View full text |Cite
|
Sign up to set email alerts
|

Applying the mental models framework to carbon monoxide risk in northern Mexico

Abstract: The mental models process was successful in developing a communication instrument capable of improving knowledge in the subject population. Future research needs include assessing the extent to which this instrument succeeds in changing behavior and reducing the risk of carbon monoxide intoxication. Future interventional efforts may focus on encouraging people to use carbon monoxide detectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…The poisoning symptoms are easily mistaken with fatigue. Depending on the exposition time and concentrations of this gas, it can be lethal or reduce lifetime, causing cardiovascular diseases and brain damage [19,20,[35][36][37][38].…”
Section: Background On Environmental Gasesmentioning
confidence: 99%
See 2 more Smart Citations
“…The poisoning symptoms are easily mistaken with fatigue. Depending on the exposition time and concentrations of this gas, it can be lethal or reduce lifetime, causing cardiovascular diseases and brain damage [19,20,[35][36][37][38].…”
Section: Background On Environmental Gasesmentioning
confidence: 99%
“…The presence of toxic gases is deadly for the birds and the workers would have enough time to leave the place without harm [15]. More recently, the detection of other gases has been studied with the purpose of avoiding incidents and accidents, as fires and explosions involving flammable gas leakages as well as providing better results from industrial processes involving chemical reactions [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research had found that the target population had little knowledge of CO alarms and frequently overestimated their price. However, a majority indicated they were willing to buy CO alarms when informed of their true price (Galada et al 2009). The EE component is important because health campaign developers and the people they seek to inform are often culturally unalike (Airhihenbuwa and Obregon 2000).…”
Section: The Entertainment-education Communications Strategymentioning
confidence: 99%
“…Finally, EE recommends researchers measure the effectiveness of their campaigns (Singhal and Rogers 1999). A pretest/posttest evaluation was used to demonstrate the effectiveness of the comic book at improving knowledge among the target population (see Galada et al 2009). Improving knowledge is not sufficient on its own to motivate behavioral change but is a necessary first step, particularly for an issue requiring a level of scientific understanding (Rogers, 2003).…”
Section: The Entertainment-education Communications Strategymentioning
confidence: 99%